TRANSLATION STRATEGIES AND IDEOLOGY IN INDONESIAN VERSIONS OF LET IT GO AND SHOW YOURSELF - Wafa Andini; Todo Sibuea (Prodi Sastra Inggris UKI, 2026)
Song translation in animated films is a complex process because it requires balancing meaning, musicality, and cultural adaptation to ensure that the lyrics remain understandable, singable, and acceptable to the target audience. This study aims to analyze the official Indonesian translations of the songs Let It Go and Show Yourself from Frozen and Frozen II by examining the translation strategies, communicative purposes, translation ideology, and audience responses to the translated lyrics. This study employed a descriptive qualitative approach through a comparative analysis of the original English lyrics and their official Indonesian versions. The analysis was supported by questionnaire data collected from 50 respondents and Spotify streaming data as an indicator of audience reception. The findings reveal that the Indonesian translations successfully maintain musical quality through linguistic naturalness, rhythm, rhyme, and singability, although several instances of semantic reduction were employed to accommodate musical constraints. Furthermore, the results indicate that domestication is the dominant translation ideology, as the translators prioritized cultural familiarity, linguistic naturalness, and ease of comprehension for Indonesian audiences over preserving source-language features. Audience responses also demonstrate positive perceptions regarding meaning clarity, cultural appropriateness, and the overall quality of the translations. This study concludes that the success of song translation is determined not only by semantic equivalence but also by the translator’s ability to balance linguistic, musical, communicative, and cultural aspects, enabling the translated songs to convey their emotional impact while remaining accessible and acceptable to Indonesian audiences.